The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/0192513x10389304
|View full text |Cite
|
Sign up to set email alerts
|

Parental Divorce and Couples’ Adjustment During the Transition to Parenthood: The Role of Parent-Adult Child Relationships

Abstract: In this study, the authors examined the associations between parental divorce, quality of relationships with parents, and dyadic adjustment during transition of 114 couples to parenthood. Data were collected during the third trimester of pregnancy and at 9 months postpartum. As predicted, the authors found that women from divorced families reported more conflict, less support, and less depth in the relationships with their fathers. However, it was the extent to which their relationships with their mothers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(96 reference statements)
0
4
0
2
Order By: Relevance
“…Empirical studies point to these factors as important, but with some mixed results and gender‐dependent findings. For new fathers (but not mothers), recalling low parental relationship quality (Belsky & Isabella, ), high levels of parental conflict (Cowan & Cowan, ), and divorce (Bouchard & Doucet, ) have predicted deteriorations in relationship outcome measures. Some work has shown that mothers' (but not fathers') recall of low parental relationship quality predicted postbirth relationship functioning (Perren, Von Wyl, Bürgin, Simoni, & Von Klitzing, ).…”
Section: The Vulnerability‐stress‐adaptation Modelmentioning
confidence: 99%
“…Empirical studies point to these factors as important, but with some mixed results and gender‐dependent findings. For new fathers (but not mothers), recalling low parental relationship quality (Belsky & Isabella, ), high levels of parental conflict (Cowan & Cowan, ), and divorce (Bouchard & Doucet, ) have predicted deteriorations in relationship outcome measures. Some work has shown that mothers' (but not fathers') recall of low parental relationship quality predicted postbirth relationship functioning (Perren, Von Wyl, Bürgin, Simoni, & Von Klitzing, ).…”
Section: The Vulnerability‐stress‐adaptation Modelmentioning
confidence: 99%
“…For example, it is well established that the children of young parents, especially teenage parents, have an increased risk for a number of adverse developmental outcomes across childhood, adolescence, and into adulthood (Fergusson & Woodward, 1999; Hardy, Astone, Brooks‐Gunn, Shapiro, & Miller, 1998; Pogarsky, Thornberry, & Lizotte, 2006). In like manner, exposure to family instability and parental adjustment problems in the family of origin predicts later marital instability and conflict and parenting difficulties (Amato & Cheadle, 2005; Bouchard & Doucet, 2011; Doucet & Aseltine, 2003). Finally, exposure to child maltreatment has been linked to later parenting strategies that are less positive and more punitive in comparison to parents not exposed to maltreatment in childhood (Banyard, 1997; Locke & Newcomb, 2004; Pears & Capaldi, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Aparentemente, esta dependencia no generaba conflicto en la pareja: ellas referían sentirse apoyadas por ellos, tanto material como emocionalmente, y ellos asumían que tenían que apoyar a sus parejas, a quienes visualizaban como más necesitadas. Aun así, no deja de ser preocupante la precariedad laboral y la falta de planificación que muestran ellas, considerando que en el primer año de vida del bebé existe un aumento en las separaciones (Bouchard & Doucet, 2011;Rijavec Klobučar, 2016), así como las mayores tasas de pobreza en hogares con jefatura femenina (Observatorio Social, 2017).…”
Section: A Propósito Del Primer Encuentro Con Las Parejasunclassified
“…La pareja, por su lado, comienza a diferenciar su relación en el subsistema romántico o marital y el subsistema parental, los cuales se influencian mutuamente (Minuchin, 1979). Se ha descrito que esta etapa constituye una crisis normativa en la vida de las personas (Frevert et al, 2008), ya que implica una serie de desafíos y ajustes, tanto personales como familiares (Cierpka et al, 2011;Moreno-Rosset et al, 2016), existiendo una mayor susceptibilidad de las parejas a separarse (Bouchard & Doucet, 2011;Rijavec Klobučar, 2016).…”
unclassified